Determinants of culinary tourism development in Pomeranian Voivodeship - Charzyński, Przemysław; Gonia, Alicja; Podgórski, Zbigniew; Kruger, Agnieszka Anna (Journal of Education, Health and Sport, 2017)
Pomeranian cuisine is characterized in the paper, It is a region in Northern Poland whose culinary heritage has been partially forgotten in the communist period, and is now being rediscovered. Typical dishes of traditional and modern Kashubian and Kociewie cuisine were presented, that can be a motivation for tourists interested in discovering and tasting of the regional dishes to visit this region. Geographical, historical and cultural heritage of Pomerania are the primary determinants of the formation of culinary trails and organization of interesting food related events, which enables the development of this type of tourism in the studied area.